Being targeted: How counter-arguing and message relevance mediate the effects of cultural value appeals on disease prevention attitudes and behaviors - Yan, Xiaodi (Frontiers in Psychology, 2022)
This study investigated the effects of cultural value appeals in health persuasion. Situated in the COVID-19 pandemic, this study examined if and how individualistic and collectivistic appeals can improve attitudes and behaviors related to the use of face masks among European Americans and Asian Americans. Results showed that for European Americans, collectivistic versus individualistic appeals were more effective to improve attitudes and behavioral intention. Perceived message relevance and counter-arguing were significant mediators explaining the effects. For Asian Americans, both individualistic and collectivistic appeals predicted significant changes in attitudinal and behavioral outcomes. These findings have important theoretical and practical implications.